A mini review of what matters in the management of NAS, is ESC the best care? - Gomez Pomar, Enrique (Frontiers in Pediatrics, 2023)
As the use of opioids and polysubstance by pregnant women has increased over the years, there has also been a sharp increase in cases of neonatal abstinence syndrome (NAS). Classically, infants affected by NAS have been cared for in neonatal intensive care units resulting in an increase of healthcare expenditure and resource utilization as well as separation from the families. Consequently, the Eat, Sleep, and Console (ESC) tool was developed and promoted as a novel method that focuses on maternal/infant dyad during hospital stay while decreasing the use of pharmacological interventions and therefore decreasing the length of stay and healthcare expenditure. Thus, it has been implemented in several hospitals in the United States. Although the training of staff has been proposed and the interventions of sleep, eat, and console are defined, there still exists a lack of standardization of this practice specifically in regard to the type of associated non-pharmacological practices as well as the reports of its short- and long-term outcomes.